Peran Akuntansi dalam Etika Bisnis Islam - Harisah; Sahi, Ahmad (Department of Islamic Accounting, The Faculty of Islamic Economics and Business, State Islamic Institute of Kediri [IAIN Kediri, 2021)
Every sharia business activity requires accurate recording to provide confidence for everyone who has an interest, the accurate recording will be read with the role of good sharia accounting so that every activity will be easy to read. Thus, this study was reviewed using a theoretical qualitative method by describing some of the results of previous studies and adequate theories. This study found that accounting is one of the activities that must be carried out by business people to reflect every transaction made that will have a positive impact on business people and all parties who need accurate data related to the business, and this accounting is also a form of ethics for business actors. a business that is by the sharia concept